2009
DOI: 10.1177/0218492309103308
|View full text |Cite
|
Sign up to set email alerts
|

Improved Combined Superior-Transseptal Approach to the Mitral Valve

Abstract: In mitral valve surgery, the combined superior-transseptal approach gives excellent exposure of the mitral valve, but it is lengthy and complex. A modified version of this approach was made without cutting the right atrial appendage and the dome of the right atrium. This shorter procedure was evaluated in 30 patients aged 4-61 years undergoing complex mitral valve operations including mitral repair (33.3%), reoperation (30%), and small left atrium (30%). The mitral valve was exposed well in all cases. Because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Significantly more patients in the STS approach group in the present study required additional operative interventions, and this accounted for the longer cardiopulmonary bypass and aortic cross‐clamp times in this group. Likewise, this study confirms the findings of previous reports that mortality rates associated with both approaches were comparable 1,11 …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Significantly more patients in the STS approach group in the present study required additional operative interventions, and this accounted for the longer cardiopulmonary bypass and aortic cross‐clamp times in this group. Likewise, this study confirms the findings of previous reports that mortality rates associated with both approaches were comparable 1,11 …”
Section: Discussionsupporting
confidence: 92%
“…Likewise, this study confirms the findings of previous reports that mortality rates associated with both approaches were comparable. 1,11 Concern continues about the STS approach leading to increased incidence of developing postoperative sinus node dysfunction or rhythm disturbances, [12][13][14][15] such as atrioventricular block, atrial flutter, or fibrillation, 4 supraventricular and junctional dysrhythmias, 9 and a higher incidence of permanent pacemaker insertion. 16 Our study confirms the presence of a significant relationship between the operative approach and sinus node dysfunction, and that patients with preoperative sinus rhythm were more likely to lose their normal sinus rhythm when the STS approach was used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite possible drawbacks including increased ischemia time, length of hospital stay, CPB, cross-clamp time, and increased bleeding related to the procedure, as previously mentioned, some authors reported no significant difference between the study groups [ 18 , 19 ] . In line with the literature, we observed no significant differences in the amount of bleeding, re-operation, and the length of hospital and ICU stay between the groups in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Calcifications around the mitral valve ring and hypertrophic right ventricle may contribute to the narrowness of the left atrium. Additionally, scars and adhesions lead to mobility loss in the mitral valve and surrounding tissues and make surgery more challenging [Orhan 2000;Nguyen 2009]. Because of the factors mentioned above, obtaining an adequate view of the mitral valve is mandatory.…”
Section: Introductionmentioning
confidence: 99%